2003
DOI: 10.1021/ol034051n
|View full text |Cite
|
Sign up to set email alerts
|

Novel Method for Incorporating the CHF2 Group into Organic Molecules Using BrF3

Abstract: 2-Alkyl-1,3-dithiane derivatives, easily made from alkyl bromides and the parent 1,3-dithiane, were reacted with BrF 3 to form the corresponding 1,1-difluoromethyl alkanes (RCHF 2 ) in 60−75% yield. The reaction proceeds well with primary alkyl halides. The limiting step for secondary alkyl halides is the relatively low yield of the dithiane preparation. The two sulfur atoms of the dithiane are essential for the reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(29 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…[61] Once in hand, the product 103 reacts well with BrF 3 producing branched difluoromethyl-secondary alkyl derivatives 104 (Scheme 26). [62] A somewhat similar idea led to the synthesis of a,a'-difluoro esters whose significance is on the rise after it was found that a,a'-difluoro ketones can serve as enzyme inhibitors. [63] Following a known procedure, [64] an alkyl bromide was reacted with the lithium salt of 99 and then with ethyl chloroformate to produce 2-alkyl-2-ethoxycarbonyl-1,3-dithiane 105.…”
Section: Forming the Cf 2 Groupmentioning
confidence: 99%
“…[61] Once in hand, the product 103 reacts well with BrF 3 producing branched difluoromethyl-secondary alkyl derivatives 104 (Scheme 26). [62] A somewhat similar idea led to the synthesis of a,a'-difluoro esters whose significance is on the rise after it was found that a,a'-difluoro ketones can serve as enzyme inhibitors. [63] Following a known procedure, [64] an alkyl bromide was reacted with the lithium salt of 99 and then with ethyl chloroformate to produce 2-alkyl-2-ethoxycarbonyl-1,3-dithiane 105.…”
Section: Forming the Cf 2 Groupmentioning
confidence: 99%
“…For the last 10 years or so, we have investigated the versatility of BrF 3 as a nucleophilic fluorinating agent, especially in constructing and attaching the CF 2 [11,12] and the CF 3 [13,14] groups to various sites in organic molecules (Scheme 1). The main feature of the mechanism governing most reactions with BrF 3 involves complexation of the soft acidic bromine around a soft base (e.g., sulfur or nitrogen atoms) in the target molecule.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, organofluorine chemistry has attracted enormous attention in the field of pharmaceutical and agricultural chemistry, as exemplified by the fact that fluorine substituents have become widespread and important drug components [8,9]. Among fluorine-containing moities, the difluoromethyl group (CF 2 H) is of significant interest [10][11][12][13], since the latter one is believed to act as an isopolar and isosteric analog of the CH 2 OH group [14,15]. Moreover, CF 2 H is able to act as a lipophilic hydrogen bond donor through hydrogen bonding [11].…”
Section: Introductionmentioning
confidence: 99%
“…There are several methods for introducing the CF 2 H moiety [4,5,7,16], including (a) the deoxofluorination of aldehydes using SF 4 , DAST, or SeF 4 reagent [17,18], (b) nucleophilic fluorination of gem-bistriflates using TBAF [19], (c) fluorination of 1,2-or 1,3-dithianes using BrF 3 [12,20,21], (d) the addition of CBr 2 F 2 to double bonds [22], (e) S RN 1 reaction between a nucleophile and CHClF 2 [5,23], and (f) nucleophilic introduction of a CF 2 H moiety into carbonyl compounds using (difluoromethyl)dimethylphenylsilane [24] or difluoro[bis(trimethylsilyl)]methane [10]. More recently, both difluoromethyl phenyl sulfone (PhSO 2 CF 2 H) and [difluoro(phenylsulfonyl)-methyl]trimethylsilane (Me 3 SiCF 2 SO 2 Ph) were used as efficient nucleophilic difluoromethylating agents for a variety of electrophiles [25].…”
Section: Introductionmentioning
confidence: 99%